RIFT BASIN DEVELOPMENT AND HYDROCARBON PLAY IDENTIFICATION OF PAKOL AREA NORTH SUMATRA BASIN - IRIANSYAH DARMAWAN, HENDRA
Pakol High area is one of hydrocarbon exploration focus area in North Sumatra Basin. Rift basin development and potential play hydrocarbon identification is essential in order to widen the exploration target. There are five identified rift basin development phase from the analysis, they are early syn-rift phase, mid syn-rift phase, late syn-rift phase, immediate post-rift phase, and late post-rift phase. The early syn-rift phase is identified based on the image on seismic that shows mounded facies and poor seismic reflector continuity. The mid syn-rift phase displays mounded, chaotic, oblique, and convergent seismic facies. The late syn-rift phase as the last phase that affected by the movement of border fault expresses oblique-shingled and chaotic seismic facies. Along with the ceassation of border fault movemment, the immediate post-rift phase was developed in this area and indicates parallel and mounded seismic facies while at several part this phase indicate toplap termination pattern. On the well data, the immediate post-rift phase demonstrate funnle shape log motives, dominated by claystone in the lower part and dominated by sandstone at the upper part which deposited in neritic to delta environment.The late post-rift as the final phase illustrates parallel seismic facies with poor reflection continuity. The late post-rift phase is dominated by claystone that deposited in middle neritic to deep marine. Every phase of basin development provides unique depositional facies. Some of the facies developed have the potential to be hydrocarbon play. The facies that identified as hydrocarbon play are fluvial, alluvial fan, talus alluvial fan, mouthbar, shallow marine, transition, and reefal facies